Estudo das propriedades microestruturais e ópticas do sistema BaO-BaF2-B2O3 - Aranha, Carolina Pereira (2011)
The objective this work is study the system BaO-B2O3 glassy-BaF2 and phases obtained from the process of controlled crystallization of it in pursuit of obtain the β-phase BaB2O4,. We studied samples containing between 0% and 40% barium fluoride. The evaluation of the microstructural and optical properties were performed using the techniques of Differential Scanning Analysis (DSC), X-ray diffraction(XRD), optical microscopy, microhardness, and absorption in the visible and ultraviolet (UV). The study of microhardness of the samples revealed an increase in tensile strength with increasing fluoride content in the sample. Increasing the fluoride content in the sample is also related to a decrease in Tg, as verified by DSC. The study of XRD patterns of crystallized samples showed that the prevalence of β-phase is BaB2O4 reduced as the fluoride content exceeds 10% of the sample, and for the sample containing 40% fluoride, the XRD patterns revealed the predominance of phase Ba2B5O9F, and samples with 20% and 40% of fluoride showed the lowest optical absorption in the visible.